Detection of Erythropoietin in Exhaled Breath Condensate of Nonhypoxic Subjects Using a Multiplex Bead Array - Christian Schumann; Kathy Triantafilou; Stefan Krueger; Vinzenz Hombach; Martha Triantafilou; Gunther Becher; Philipp M. Lepper (Mediators of Inflammation)
As a noninvasive method, exhaled breath condensate (EBC) has gained importance to improve monitoring of lung diseases and to detect biomarkers. The aim of the study was to investigate, whether erythropoietin (EPO) is detectable in EBC. EBC was collected from 22 consecutive patients as well as from healthy individuals. Using a multiplex fluorescent bead immunoassay, we detected EPO in EBC, as well as tumour necrosis factor-α (TNF-α) in 13 out of 22 patients simultaneously (EPO 0.21 ± 0.03 in U/mL and TNF-α 34.6 ± 4.2 in pg/mL, mean ± SEM). No significant differences for EPO levels or correlation between EPO and TNF-α were found but TNF-α was significantly higher in patients with chronic obstructive pulmonary disease (COPD) than in non-COPD (obstructive sleep apnoea, OSA, and lung healthy patients). This is the first report of detection of EPO in EBC. Due to the small study size more data is needed to clarify the role of EPO in EBC.